Effect of Problem Based Learning Scenario on Knowledge of Third Class Students About Childhood Poisoning - Nazan Karaoğlu; Sevgi Pekcan; Burak Cem Soner; Muzaffer Şeker; Rahmi Örs (Güncel Pediatri)
Introduction: It is stated that students cannot carry their knowledge on basic medical sciences that they gained with classical education to clinical classes and clinical practice and problem based learning (PBL) can compensate this drawback. It was aimed to evaluate the effect of PBL scenario written on this topic on level of knowledge about childhood poisoning of third class students who completed the most of theoretical pharmacology education.Materials and Method: A questionnaire form prepared by researchers was applied to randomly chosen PBL groups without writing names and on the basis of voluntariness before and after a case of childhood poisoning which was applied as the second PBL scenario in the second midterm of 2009-2010 academic years. Numbers, percentages, chi-square and student’s t-test were used for evaluation of the questionnaire form comprised of demographic data, open-closed ended questions for measuring attitudes and level of knowledge against case of poisoning and statements as making a priority ranking.Results: In the study group, 89 students took part in pre-test and 96 students took part in post-test. In the answers to the list including the substances that are the most common causes of admission according to data of Refik Saydam National Poison Center (e.g. lotion, bath foam, cosmetics, water color and calamine lotions), the substances that the students stated to be toxic in pre-test were answered correctly in the post-test (p<0.05). Number of correct answers increased significantly for knowledge about commonly used drugs in clinical practice like anti-depressants, calcium canal blockers, oral antidiabetics that were marked as non-toxic by the students although they are toxic (p<0.05). While mean knowledge score for these 40 items was 17.52±5.82 in pre-test, it increased to 27.89±8.79 in post-test (p<0.001).Conclusion: Results of this study indicate that PBL scenario applied to the students who learned pharmacology theoretically led increase of knowledge in terms of childhood poisoning. (Journal of Current Pediatrics 2011; 9: 68-74)